Insecticides and Wildlife - John L. Capinera (EDIS)
When we use chemical insecticides to eliminate problem insects, we discover that the effects of insecticides are not always limited to these 6-legged targets. Wildlife, pets, and humans also can be affected by insecticides. So, one of the great challenges confronting humans is to develop ways to manage insects without affecting non-target organisms. Learn more in this 16-page fact sheet written by John L. Capinera and published by the UF Department of Entomology and Nematology, October 2011.